2020
DOI: 10.1002/pbc.28607
|View full text |Cite
|
Sign up to set email alerts
|

The state of the science for communication training in pediatric oncology: A systematic review

Abstract: Within the field of pediatric oncology, communication skills training (CST) has been recognized as a high priority by professional and accrediting organizations. However, the effectiveness of formalized CST interventions for pediatric oncology providers remains poorly understood. We systematically searched PubMed, Web of Science, Scopus, and PsycInfo for original research articles assessing the effectiveness and quality of CST interventions targeting pediatric oncology clinicians. From 971 deduplicated referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Kaye et al. identified six published interventions, all from the United States 44 . Interventions included didactic workshops, case‐based role play, and bereaved parent teachings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaye et al. identified six published interventions, all from the United States 44 . Interventions included didactic workshops, case‐based role play, and bereaved parent teachings.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of communication with the child with advanced disease about disease, palliative care, and EOL, the persisting communication barriers, and the lack of training reported, evidence‐based effective interventions should be offered to pediatric oncology HCPs. These may be established on theory, pedagogy, 44 and inductively, utilizing the vast clinical experience of HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, few interventions have been studied in pediatric oncology. 25 Recent review articles identified only 6 communication interventions in pediatric oncology 25,26 but 88 interventions in adult oncology. 25 Furthermore, these pediatric interventions were communication skills workshops, which target primarily individual-level barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Although difficult conversations have not been formally defined as a "procedure" in medicine, the medical community, including the Accreditation Council of Graduate Medical Education and other medical subspecialty societies, recognizes communication training as a priority [ 7 , 8 ]. Several communication training methods have been studied in different clinician populations: simulation, role-play, the use of cognitive maps, checklists, as well as deliberate practice and feedback have all been shown to improve performance or self-efficacy in navigating difficult conversations [ 9 - 19 ]. Specifically, the VitalTalk [ 20 ] curriculum enhances communication skills while increasing the frequency of empathic behaviors [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%